2017
DOI: 10.1525/elementa.246
|View full text |Cite
|
Sign up to set email alerts
|

From silent spring to silent night: Agrochemicals and the anthropocene

Abstract: Hayes, TB and Hansen, M 2017 From silent spring to silent night: Agrochemicals and the anthropocene. Elem Sci Anth, 5: 57, DOI: https://doi.org/10.1525/elementa.246 IntroductionWe are in the Anthropocene and likely experiencing the Earth's sixth mass extinction. The current mass extinction is the first to be caused by a single species, humans. Chemical contaminants in the environment, especially pesticides, are playing an important role in the Anthropocene. Over 85,000 synthetic chemicals exist today (USEPA, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 291 publications
(130 reference statements)
0
67
0
1
Order By: Relevance
“…Generally, the industries that pollute more or that are environmentally sensitive companies tend to have higher levels of CED [35][36][37]. Concern over the agrochemical industry's role in environmental degradation and pollution has led to strict environmental standards for the production and the use of agricultural chemicals [31,38]. Many health and safety concerns continue to persist around the agrochemical industry, including impacts to wildlife, water contamination, and human health effects [33,38].…”
Section: Background: the Agrochemical Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the industries that pollute more or that are environmentally sensitive companies tend to have higher levels of CED [35][36][37]. Concern over the agrochemical industry's role in environmental degradation and pollution has led to strict environmental standards for the production and the use of agricultural chemicals [31,38]. Many health and safety concerns continue to persist around the agrochemical industry, including impacts to wildlife, water contamination, and human health effects [33,38].…”
Section: Background: the Agrochemical Industrymentioning
confidence: 99%
“…Concern over the agrochemical industry's role in environmental degradation and pollution has led to strict environmental standards for the production and the use of agricultural chemicals [31,38]. Many health and safety concerns continue to persist around the agrochemical industry, including impacts to wildlife, water contamination, and human health effects [33,38]. Most of the impacts on human health occur in high-risk populations in developing countries, including primary workers in production plants and residents in rural areas [33,39].…”
Section: Background: the Agrochemical Industrymentioning
confidence: 99%
“…The high diversity of the chemical compounds, complex pathways in the environment and the multitude of possible impacts may result in synergistic, additive, and antagonistic interactions (Fischer et al, 2013;Cheloni and Slaveykova, 2018). A more systematic approach taking into consideration the combined pressure of multiple stressors (Kaushal et al, 2018) and reconceptualization of distribution and transformation processes of chemical mixtures was thus advocated to be critical to ecosystem management (Hayes and Hansen, 2017). Going beyond by further exploring the novel entities dynamics in the environment within the context of climate change and increasing anthropogenic pressure on the environment will be a central topic for the future.…”
Section: Understanding the Biogeochemical Dynamics Of "Novel Entities"mentioning
confidence: 99%
“…However, the environmental evaluation and effects on human health related to glyphosate use shows its weaknesses in a worldwide context of increased use of this herbicide. Hayes and Hansen (2017) based on their analysis on the current use of agrochemicals highlighted that glyphosate is a powerful endocrine disruptor, which alters the structure of ovaries and affects the sexual differentiation and regulation of sexual steroid production. These authors also reported that masculine fertility decreases since glyphosate causes necrosis and apoptosis in testicular cells.…”
Section: Introductionmentioning
confidence: 99%